Pengaruh Harga Dan Ketepatan Waktu Terhadap Kepuasan Konsumen Satria Antaran Prima (SAP) Express Di Kota Bima - Al Akbar; Muhajirin; Puji Muniarty (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2022)
The service business is currently very much needed in the daily activities of consumers. This has resulted in consumers choosing a place for courier delivery services that can be trusted, providing affordable prices and the best timeliness, making it easier for consumer activities in term of distributing goods over long distances to be channeled properly. This study aims to determine the effect of price and timeliness on consumer satisfaction at satria antaran prima (SAP) express in bima city. This study uses multiple linear regression analysis. The population used is by all people with respondent criteria, namely consumer who visit the bima city SAP express service at least 2 times. The sample members used were 96 people who were taken by purposive sampling technique. Test results (f test) show price and timeliness simultaneously have a significant effect on consumer satisfaction of satria antaran prima (SAP) express in bima city. The result of the partial test (t test) show that price and timeliness have a significant influence on consumer satisfaction of satria antaran prima (SAP) express in bima city.